The psychological consequences of Sudden Infant Death Syndrome (SIDS) for the family system: A systematic review - Gandino, Gabriella; Diecidue, Alessia; Sensi, Annalisa; Venera, Ester Maria; Finzi, Sarah; Civilotti, Cristina; Veglia, Fabio; Di Fini, Giulia (Frontiers in Psychology, 2023)
The Sudden Infant Death Syndrome (SIDS) is a tragic and difficult experience for families. It involves not only the death of the baby but also the loss of a future as a parent, sibling or grandparent. The subsequent grief is multifaceted and each family member has different needs and resources. Through a systematic review of literature, we identified 24 studies between 1982 and 2021: they dealt with individual, family and couple experience when a SIDS occurs; in addition, some studies compared perinatal loss and neonatal loss with SIDS loss. Our results point out the need for an intervention that focuses on the needs of each family member and tailored around the specifics of SIDS loss rather than general grief.